If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 29 = a + 7 Reorder the terms: 29 = 7 + a Solving 29 = 7 + a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1a' to each side of the equation. 29 + -1a = 7 + a + -1a Combine like terms: a + -1a = 0 29 + -1a = 7 + 0 29 + -1a = 7 Add '-29' to each side of the equation. 29 + -29 + -1a = 7 + -29 Combine like terms: 29 + -29 = 0 0 + -1a = 7 + -29 -1a = 7 + -29 Combine like terms: 7 + -29 = -22 -1a = -22 Divide each side by '-1'. a = 22 Simplifying a = 22
| v=15x^3+52x^2+32x | | -12t-28=9t+47-(-4t) | | 3v+4=19 | | x^2+20x+42=0 | | 2x+72=12-3x | | 0.8+0.25x=0 | | 9(x-6)=6-30 | | 4q+-24=12 | | x+9f+10=5j | | 15(3x+1)-243(5x-2)=0 | | 25/x+6=5/6 | | 1n-1=18 | | -9x+7y=2 | | -19w+-20=18 | | c-2y=24 | | -13x+6=-12-9 | | x-2-(3+(7-2x))=-6 | | 0.625x(a-2)=10 | | 5x+2=8x+11 | | x+7+2x+3-40=0 | | 4(4x+25)-3(4x-1)=5(4x-7) | | 2x-(5-(3x+4))=x-5 | | (5c-4c)+(c-3c)= | | 5(12-3x)+x=3(-2x+4) | | x=(x+1)*0.62 | | 0=ln(6x) | | 11=-16+7w | | 79-2x=9-9x | | 4x+9=-54+11x | | b+2=11-b/4 | | 1+8x=-6+x | | 0.4+(0.35e)= |